Forensic investigation of electrocution: Examining electrical injury profiles in Hyderabad, Pakistan - Salman Ahmed Kazi; Naveed Ali Qadir; Amna Mangi; Ishrat Bibi; Waheed Ali Nahyoon; Muhammad Owais Qurni; Kumail Raza (Journal of Shalamar Medical & Dental College)
Background: Electrocution-related deaths in Pakistan are a significant public health concern, demonstrating the interplay of electrical safety, infrastructural issues, and socioeconomic status.